On determination of input parameters of the mass transfer process by fuzzy approach. - Maan, Normah; Talib, Jamalludin; Arshad, Khairil Annuar; Ahmad, Tahir (Department of Mathematics, Faculty of Science, 2005)

(untitled)
Inverse problems are natural in many real world applications including industrial chemical engineering problems. In this paper, an inverse problem in determining the value of input parameters for a desired value of output parameters of mass transfer process in the 23 stages Rotating Disc Contactor (RDC) column is considered. Hence, an inverse model describing the process in obtaining the solution of the problem is developed. The model involves only the process of mass transfer of a single drop of size assumed to be smaller then the critical drop size, in multiple stages RDC column. This is an extension of the work done on the mass transfer process of a single drop in single stage RDC column. The algorithm is based on fuzzy approach and the assumptions made in mass transfer process as adopted in previous work are also being used. The presented algorithm yields results such that the norm between the actual outputs obtained from the approximate solution and the target output is less than 10%. The algorithm is also capable of determining the optimal values of the input parameters. This inverse model has successfully eliminated the trial and error aspect of the forward process in determining the correct inputs for the desired outputs.